Pengembangan Model Pembelajaran Inovatif Mata Kuliah Riset Operasional Di Program Studi Agribisnis - Edison, Edison; Sri Nurchaini, Dewi (JALOW | Journal of Agribusiness and Local Wisdom, 2022)
This study aims to develop an innovative learning model for production-oriented competency-based operations research courses that are suitable for use in innovative learning to improve student learning outcomes in operations research courses. This research is expected to produce (1) learning models to improve production-oriented student competencies; (2) the learning model can effectively improve learning outcomes in learning; (3) the learning model can create a learning climate that positions students as learning centers with all the activities they do, motivates student learning through constructive ideas, encourages and awakens the courage to study and work based on high commitment and discipline, increase the speed of learning , learning motivation, enthusiasm for learning, teamwork, creativity, and innovation. This research is planned to be carried out in the 2021/2022 odd semester lecture activities in the operational-research course of the Agribusiness Study Program, Faculty of Agriculture, Jambi University. Participants who will take part in this research activity are planned as many as 40 students. The model used is the ADDIE model which stands for Analysis, Design, Development or Production, Implementation or Delivery and Evaluations. The results showed that lecture activities without being provided with an understanding of learning about product orientation got relatively lower final results compared to students who had been provided with an understanding of product-oriented learning. The results of research on student opinions on learning media problems and learning implementation show that manual calculation of completion is no longer relevant, unattractive and not representative anymore.